Sinonasal Outcome After Endoscopic Transnasal Surgery—A Prospective Rhinological Study. Issue 3 (12th March 2023) - Conrad, Jens; Blaese, Marco; Becker, Sven; Huppertz, Tilman; Ayyad, Ali; Ringel, Florian
Abstract : BACKGROUND: The sinonasal outcome after transnasal skull base surgery has often been neglected aside from major outcome criteria as extent of tumor resection, ophthalmological, and endocrinological parameters. OBJECTIVE: To analyze rhinological outcome after endoscopic transnasal neurosurgery. METHODS: Patients were treated using a middle turbinate–preserving transnasal endoscopic approach for sellar/parasellar lesions. As major variables, olfactory function and nose breathing ability were assessed. The study participants were investigated by odor testing ("Sniffin' sticks"), rhinomanometry, and endoscopic inspection of the nasal cavity before and 6 months after surgery. Furthermore, sinonasal-associated quality of life was measured before, immediately and 6 months after surgery with a standardized questionnaire (SNOT-20-GAV). RESULTS: Eighty-two patients (47 male, 35 female, median age 55 years) matched the inclusion criteria. Before surgery, the average odor was found to be 30.75 (≥31 = normosmia); in the postinterventional examination at 6 months, the average increased to 33.08 (n.s.). Rhinomanometric examination of binostril nasal airflow showed an average of 590.42 mL/s on inspiration before and an increase to 729.78 mL/s at 6 months after surgery. SNOT-20 symptom scores had a maximum score right after and no difference at 6 months after surgery (scores 23.76 and 14.91 vs 15.53 before surgery). CONCLUSION: Based on the study, the endoscopic transnasal technique preserving the middle turbinate has no significant negative effects on the rhinological outcome. Abstract :